Isolation of Trueperella pyogenes in heifer lung (Research, Society and Development, 2023)
The present report describes the identification of Trueperella pyogenes, an Actinobacteria of clinical relevance that has been subject to taxonomic changes in recent years, associated with a wide variety of pathological conditions, such as mastitis, metritis and pneumonia, which may be associated with immunosuppressed patients and/or those submitted to stressful conditions. However, its zoonotic character is still not well defined. The present case report describes the identification of Trueperella pyogenes, from a lung fragment from a heifer that died under suspicion of Bovine Pulmonary Disease (BPD). The fragment was sent to the FMVA Microbiology Laboratory for the realization and identification of the etiologic agent. After culture on Blood Agar and Mac Conkey in microaerophilic conditions for a period of 48 hours with daily monitoring, it was observed the pure and exuberant growth of small colonies that presented translucent pigmentation, surrounded by a halo of β-hemolysis, and that the microscopy showed gram positive bacilli of the “coryneformes” type. After carrying out the biochemical and differential tests, it was concluded that it was Trueperella pyogenes.